2007
DOI: 10.1177/002242940705500202
|View full text |Cite
|
Sign up to set email alerts
|

Peer Mentoring in a High School Jazz Ensemble

Abstract: The use of peer mentoring in a successful high school jazz band was explored during one academic year of instruction using ethnographic techniques. Participants included primary informants (student jazz band members, director, assistant director, adult mentors) and secondary informants (guidance counselor, principal, parents, nonjazz band member students). Data analysis revealed that peer mentoring contributed to the success of a high school jazz band. Five themes emerged: (a) mentoring from the adult perspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(78 citation statements)
references
References 8 publications
1
77
0
Order By: Relevance
“…Teachers also reported that while some students were initially reluctant to adopt a collaborative approach, a majority of the reluctant students did begin to work together after several sessions. These findings also are noted by Goodrich (2007) and Darrow et al (2005), who suggest that all students do not readily adopt PAL. Teachers also indicated that PAL might be even more successful if experiences were reduced in frequency and spread out over a longer period of time.…”
Section: Implications For Teachingsupporting
confidence: 55%
“…Teachers also reported that while some students were initially reluctant to adopt a collaborative approach, a majority of the reluctant students did begin to work together after several sessions. These findings also are noted by Goodrich (2007) and Darrow et al (2005), who suggest that all students do not readily adopt PAL. Teachers also indicated that PAL might be even more successful if experiences were reduced in frequency and spread out over a longer period of time.…”
Section: Implications For Teachingsupporting
confidence: 55%
“…The following quote by educational scholar Audrey Gartner captures the sentiment of teaching being a powerful form of learning (Gartner, 1998: p. 281 According to collaborative learning experts Keith Topping and Stewart Ehly, peer-assisted learningan instructional arrangement where peers help each other to gain knowledge and skill through active help and supportentails individuals sharing knowledge until it becomes a common possession (Topping & Ehly, 2001). Many researchers in music education have presented evidence that peer-assisted learning (PAL) often leads to meaningful gains in music achievement, student engagement, self-concept, and motivation to learn (Alexander & Dorrow, 1983;Darrow, Gibbs, Wedel, 2005;Goodrich, 2007;Johnson, 2011;Johnson, 2013). Additionally, PAL is a way for teachers to create a community of learners where the "open flow of ideas," the "faith in the individual and the collective," and the use of "critical reflection to evaluate problems," are all cultivated aspects of student experience.…”
Section: Introductionmentioning
confidence: 99%
“…Peer mentoring has been another focus of research in American jazz bands (Goodrich, 2007). Jazz researchers have studied pedagogies specific to improvisation (Watson, 2010;Prouty, 2008;Wehr-Flowers, 2006) and gender and improvisation (Wehr-Flowers, 2006).…”
Section: Jazz In Secondary Schoolsmentioning
confidence: 99%